1995
DOI: 10.1172/jci118005
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocyte growth and development factor. Analyses of in vitro effects on human megakaryopoiesis and endogenous serum levels during chemotherapy-induced thrombocytopenia.

Abstract: The present study shows that recombinant human megakaryocyte growth and development factor (r-HuMGDF) behaves both as a megakaryocyte colony stimulating factor and as a differentiation factor in human progenitor cell cultures. Megakaryocyte colony formation induced with rHuMGDF is synergistically affected by stem cell factor but not by interleukin 3. Megakaryocytes stimulated with rHuMGDF demonstrate progressive cytoplasmic and nuclear maturation. Measurable levels of megakaryocyte growth and development facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
104
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(110 citation statements)
references
References 24 publications
4
104
2
Order By: Relevance
“…20 Because serum TPO levels are very low in humans and difficult to quantify, levels have generally been estimated indirectly by the bioassay of megakaryocyte stimulating activity 16 or by the proliferation assay of TPO-responsive cell lines. 17,21 In these bioassays, non-specific stimulators or inhibitors in the blood samples may affect the estimation. Recently, Emmons et al 19 reported a receptor captured enzyme immunoassay for TPO in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Because serum TPO levels are very low in humans and difficult to quantify, levels have generally been estimated indirectly by the bioassay of megakaryocyte stimulating activity 16 or by the proliferation assay of TPO-responsive cell lines. 17,21 In these bioassays, non-specific stimulators or inhibitors in the blood samples may affect the estimation. Recently, Emmons et al 19 reported a receptor captured enzyme immunoassay for TPO in humans.…”
Section: Discussionmentioning
confidence: 99%
“…16 Also in human studies, TPO levels changed reciprocally to platelet counts in patients with cyclic thrombocytopenia or undergoing bone marrow transplantation after myeloablative therapy. [21][22][23][24] On the other hand, it was described that TPO levels were high when thrombocytopenia was due to megakaryocyte deficiency, and low when due to increased platelet destruction, 19 and that serum megakaryocyte colony-stimulating activity levels appeared to be inversely related to marrow megakaryocyte numbers. 25 In the present study, we could clearly demonstrate using a sensitive ELISA that human TPO levels also changed inversely with the number of platelets after myelosuppressive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…TPO stimulates the growth of committed megakaryocyte progenitors, the progressive maturation of megakaryocytes, and proplatelet formation [2][3][4][5][6][7][8]. In addition to its stimulating effect on megakaryocytopoiesis, TPO has also been reported to affect committed erythroid progenitors [9], hematopoietic progenitor cells [10], and leukemia cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…TPO supports the formation of megakaryocyte colonies from murine bone marrow cells and human CD34 + cells in semisolid cultures [19,[25][26][27][28][29][30][31]. TPO also serves as a potent megakaryocyte maturation factor, because megakaryocytes generated in liquid culture containing TPO exhibit a marked increase in ploidy classes and well-developed demarcation membranes in their cytoplasm [26,27,29,31].…”
Section: Introductionmentioning
confidence: 99%